2017
DOI: 10.1101/215178
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spontaneous eye blink rate and dopamine synthesis capacity: Preliminary evidence for an absence of positive correlation

Abstract: Dopamine is central to a number of cognitive functions and brain disorders. Given the cost of neurochemical imaging in humans, behavioral proxy measures of dopamine have gained in popularity in the past decade, such as spontaneous eye blink rate (sEBR). Increased sEBR is commonly associated with increased dopamine function based on pharmacological evidence and patient studies. Yet, this hypothesis has not been validated using in vivo measures of dopamine function in humans. In order to fill this gap, we measur… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…First, the assumption of a positive correlation between sEBR and dopamine levels in striatum in humans is still under debate. In a recent preprint, Sescousse et al, (2017) found a negative relation between sEBR and dopamine synthesis capacity as assessed with [ 18F]DOPA PET in a mixed sample of gamblers and control participants. Dang et al (2017) found no significant correlation between D2/3 receptor availability and sEBR in humans.…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the assumption of a positive correlation between sEBR and dopamine levels in striatum in humans is still under debate. In a recent preprint, Sescousse et al, (2017) found a negative relation between sEBR and dopamine synthesis capacity as assessed with [ 18F]DOPA PET in a mixed sample of gamblers and control participants. Dang et al (2017) found no significant correlation between D2/3 receptor availability and sEBR in humans.…”
Section: Limitationsmentioning
confidence: 99%
“…However, in pathological gamblers, striatal D2/3-receptor availability was associated with mood related impulsivity and gambling severity (Clark et al, 2012;Boileau et al, 2013). In addition, van Holst et al (2017) found increased striatal dopamine synthesis capacity, as assessed with [ 18 F]fluoro-levodihydroxyphenylalanine ([ 18 F]DOPA) PET, in gamblers compared with controls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Общепринятая теория состоит в том, что де-фицит дофамина приводит к снижению частоты моргания (брадикинезия моргания) и усилению аномального незавершенного моргания. Однако к этой гипотезе надо относиться осторожно, поскольку недавние исследования показали, что частота моргания не связана со способностью к синтезу дофамина [14]. Нарушение моргания в свою очередь вызывает гиперосмолярность слезной пленки, ускоренное испарение слезы и повреждение роговицы [15].…”
unclassified